2019
DOI: 10.1186/s12882-019-1307-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between prediabetes (defined by HbA1C, fasting plasma glucose, and impaired glucose tolerance) and the development of chronic kidney disease: a 9-year prospective cohort study

Abstract: Background The aim of the present study was to investigate the clinical impact of prediabetes on the development of incident chronic kidney disease (CKD) in a Korean adult population, using data from the Korea Genome and Epidemiology Study. Methods This prospective cohort study included 7728 Korean adults without baseline CKD and type 2 diabetes. Prediabetes was defined by impaired fasting glucose (IFG), impaired glucose tolerance (IGT), and HbA1 C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 36 publications
3
21
0
Order By: Relevance
“…For some years, evidence for a correlation between an increased risk of chronic kidney disease (CKD) and diabetic kidney disease (DKD) in prediabetes has been recorded [ 35 , 46 ]. Characteristic features found in 14 cohort studies are summarized in Table 2 [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Half of the studies [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ] were designed mainly to assess the relationship between metabolic syndrome and CKD.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For some years, evidence for a correlation between an increased risk of chronic kidney disease (CKD) and diabetic kidney disease (DKD) in prediabetes has been recorded [ 35 , 46 ]. Characteristic features found in 14 cohort studies are summarized in Table 2 [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Half of the studies [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ] were designed mainly to assess the relationship between metabolic syndrome and CKD.…”
Section: Methodsmentioning
confidence: 99%
“…The size of groups in the presented cohorts ranged from 2398 to 118,924. The European population [ 55 , 56 , 58 ] and the American population [ 47 , 48 , 50 ] were each assessed in three studies, while eight studies concerned the Asian population [ 49 , 51 , 52 , 53 , 54 , 57 , 59 , 60 ]. Some of the European and American studies included multi-ethnic populations, but the white population constituted at least 50% in each of them.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 17 Fasting plasma glucose (FPG) and 2-hour plasma glucose (2hPG) have been commonly used for the diagnosis of diabetes; and recently, glycated hemoglobin A 1c (HbA 1c ), a measure of long term glucose homeostasis, has also been recommended for diagnosis of diabetes. The KORA study suggested that FPG, 2hPG and HbA 1c were all associated with CKD 15 ; however, studies from China, Japan and Korea indicated that it was elevated HbA 1c or impaired glucose tolerance (IGT), but not impaired fasting glucose (IFG) increased the risk for CKD, [18][19][20] and one study based on the Systolic Blood Pressure Intervention Trial concluded that FPG was not associated with the development of CKD. 21 Therefore, which of these prediabetic glycemic indices is/are genuinely associated with the occurrence of CKD remain unclear.…”
Section: What Are the New Findings?mentioning
confidence: 99%
“…34 35 A most recent prospective cohort study from Korea also found that prediabetes was a risk factor for CKD. 20 To the contrary, another cross-sectional 36 and a cohort study 37 suggested otherwise, which is that prediabetes is not a risk factor for CKD. What could be the reason for these discrepancies?…”
Section: Epidemiology/health Services Researchmentioning
confidence: 99%